Hipersuperfícies rotacionais com curvatura escalar constante em espaços de curvatura constante. - Vitório, Feliciano Marcílio Aguiar (1995)
In this work we present a classification theorem for the rotational hypersurfaces with constant scalar curvature in the space forms due to M.Leite. We impose the constant scalar curvature condition to obtain classification theorems for such hypersurfaces.